(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This research is an in-depth study of the role of artificial intelligence in developing teaching methods in UAE universities, highlighting the University of Sharjah as an applied model. The research aims to explore how artificial intelligence technologies are applied in higher education, and to analyze their impact on the quality of education and teaching methods. By adopting a comprehensive methodology that combines a descriptive, analytical approach and a comparative approach, the research addresses the technical and organizational challenges associated with the adoption of artificial intelligence in the university environment. It also reviews successful cases and potential future applications, based on case studies and in-depth analyzes of educational environments based on artificial intelligence. The results show that the application of artificial intelligence can radically transform the university education experience by providing personalized educational experiences that match the needs of each student, and developing immediate and accurate assessment tools that provide real-time feedback to improve academic performance. In addition, artificial intelligence contributes to enhancing collaboration between students through interactive educational platforms and providing immersive learning environments that use virtual and augmented reality technologies. The study emphasizes the need to invest in technical infrastructure and develop comprehensive regulatory policies, in addition to training educational personnel to use these technologies efficiently. The research concludes by providing practical recommendations to enhance the use of artificial intelligence in university education, which contributes to achieving sustainable progress and developing a more adaptive and innovative educational system.